Empathetic attitudes of undergraduate paramedic and nursing students towards four medical conditions: A three-year longitudinal study. (February 2015) - Williams, Brett; Boyle, Malcolm; Fielder, Chris
Summary: Introduction: In the healthcare context empathy is the cognitive ability to understand a patient's perspectives and experiences and to convey that understanding back to the patient. Some medical conditions are frequently stigmatised or otherwise detrimentally stereotyped with patients often describing healthcare practitioners as intolerant, prejudiced and discriminatory. Objectives: The purpose of this study was to find how a group of paramedic students and nursing/paramedic double-degree students regard these types of patients and to note any changes that may occur as those students continued through their education. Methods: The 11-questions, 6-point Likert scale version of the Medical Condition Regard Scale was used in this prospective cross-sectional longitudinal study. This study included paramedic students enrolled in first, second, third and fourth year of an undergraduate paramedic or paramedic/nursing program from Monash University. Results: A total of 554 students participated. Statistically significant differences were found between double-degree and single-degree students ( p < 0.0001), year of course ( p < 0.0001) and gender ( p = 0.02) for patients presenting with substance abuse. Similar results were found for patients with intellectual disability and attempted suicide. No statistically significant results were found for acute mental illness. Conclusions: This study has demonstrated significant differences in empathy between paramedic and nursing/paramedic double-degree students in regard to patients with these complex medical conditions. Paramedic/nursing students generally showed a positive change in empathy towards these complex patients by their third year of study; however, they also showed some alarming drops in empathy between second and third year.